Application of a Vegetation Health Index to Identify Distribution of Agricultural Drought in Diyala Province, Iraq - Ahmed, Bushra A.; Hadid, Rana S. (Iraqi Journal of Science, 2025)
Over two decades, this study analyzes drought trends in Diyala Province, Iraq, and It utilizes remote sensing data and rainfall analysis to evaluate the severity and frequency of drought in 2002, 2005, 2010, 2015, 2020, and 2022. The research maps drought distributions in Diyala Province using satellite images from Landsat 7, Landsat 8, and Landsat 9 and analyzes the vegetation health index (VHI), soil moisture index (SMI), and average rainfall data. Results showed increased drought intensity: severe drought expanded from 48% in 2005 to 50% in 2022, and arid conditions increased from 1.1% in 2002 to 17.1% in 2022, as per SMI. Moreover, rainfall analysis reveals varying patterns, with 2022 experiencing lower average rainfall (4.215 mm) and higher variability (1.4633 mm standard deviation) compared to 2015 (6.735 mm, 1.1227 mm). The discoveries, pivotal for agriculture and water management, underscore the necessity of consistent monitoring and adaptable strategies for addressing shifting climate patterns.